2015
DOI: 10.1111/mms.12238
|View full text |Cite
|
Sign up to set email alerts
|

Prey use and nutritional differences between reproductive states and age classes in Atlantic spotted dolphins (Stenella frontalis) in the Bahamas

Abstract: Nutritional quality of prey is a significant driver of predator foraging patterns. In mammals, nutritional needs are known to change across ontogeny and reproductive state; however, little is known about nutrition in marine mammals. For this study, we used observational data of diurnal foraging events, collected annually from 1992 to 2009, to investigate nutrition and prey use in Atlantic spotted dolphins (Stenella frontalis) on Little Bahama Bank, Bahamas, between reproductive states (lactating, pregnant, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Drastic shifts in climate-related regimes are believed to be responsible for the decrease in availability of high-quality prey species (in terms of energy and lipid contents) and an increase in lowquality foods, which has negatively influenced marine predator populations around the world (Österblom et al 2008). Operating in such a complex environment, marine predators require particularly sophisticated foraging strategies that enable them to balance self-and offspring-feeding, and also in many circumstances simultaneously consider the nutritional constraints of their partners (Weimerskirch et al 1994;Machovsky-Capuska et al 2014a;Malinowski and Herzing 2015). Seabird chicks are under constant age-related fluctuations in lipid, protein, water and energy density until they reach functional maturity and are able to feed for themselves (Navarro 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Drastic shifts in climate-related regimes are believed to be responsible for the decrease in availability of high-quality prey species (in terms of energy and lipid contents) and an increase in lowquality foods, which has negatively influenced marine predator populations around the world (Österblom et al 2008). Operating in such a complex environment, marine predators require particularly sophisticated foraging strategies that enable them to balance self-and offspring-feeding, and also in many circumstances simultaneously consider the nutritional constraints of their partners (Weimerskirch et al 1994;Machovsky-Capuska et al 2014a;Malinowski and Herzing 2015). Seabird chicks are under constant age-related fluctuations in lipid, protein, water and energy density until they reach functional maturity and are able to feed for themselves (Navarro 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Since the abundance of dolphins is lower during winters (Smith et al, 2013;Sprogis et al, 2016a), it was hypothesized that prey quantity would be also be lower, but that prey quality would be relatively higher to support the mothers and calves that remain in local waters throughout the winter (Smith et al, 2016), as the energetic cost of lactation and growth is high (Malinowski and Herzing, 2015). As hypothesized, the highest energy contents of fish were generally found in the winter: the highest KJ in traps and gillnets were found in the winter season; while the energy content in the seine net was similar in summer and winter.…”
Section: Seasonal Energy Content and Prey Qualitymentioning
confidence: 99%
“…While prey density has long been associated with prey profitability for a predator, prey quality has been quantified in foraging models only in recent years (Spitz et al, 2010b) and has been seen to be a significant factor in determining cetacean foraging patterns (Malinowski and Herzing, 2015). The quality of prey can be measured by nutrient composition and digestibility, which is often measured by energy density or kilo joules per gram (KJ/g) (Spitz et al, 2010a(Spitz et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that vertebrate predators consume prey that varies in their nutritional and energetic compositions (Lenky, Eisert, Oftedal, & Metcalf, ; Machovsky‐Capuska, Coogan, Simpson, & Raubenheimer, ; Machovsky‐Capuska, Priddel et al., ; Malinowski & Herzing, ; Mayntz et al., ). Here, we demonstrated that there is an appreciable variation in the proportional wet mass contribution of P, L, W and PL ratio in the prey species consumed by gannets, which is consistent with previous findings on gannet prey species (Machovsky‐Capuska, Senior, Benn et al., ; Tait et al., ).…”
Section: Discussionmentioning
confidence: 99%